Step-by-step explanation:
For a function ...
y = f(x)
the inverse function is ...
x = f(y)
To write that in the form y=f^-1(x), you need to solve for y.
__
For your function f(x) = e^x +3 this looks like ...
x = e^y +3
x -3 = e^y . . . . . subtract 3
ln(x -3) = y . . . . . take the natural log
So, we can write ...
f^-1(x) = ln(x -3)
_____
Attached is a graph of these functions. As you might guess from the interchange of x and y, a function and its inverse are mirror images of each other across the line y=x.